Does Job Satisfaction Mediate the Effect of Supervisor Performance and Work Environment on Personnel Performance in Police Department? - Damayanti, Alviana Sukma; Sutarmin, Sutarmin (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2025)
Police institution top management needs to use various factors effectively to support improvements in the performance of police personnel, including supervisor performance, work environment, and personnel job satisfaction. This study then aimed to determine the influence of these three factors in relation to personnel performance in police institutions in Indonesia, especially in the Surabaya Police Criminal Investigation Unit. The research approach was quantitative, with the research sample set at 82 personnel in the Surabaya Police Criminal Investigation Unit. The data that has been collected was then analysed using path analysis using the SmartPLS program. The results of the study showed that supervisor performance has a significant and positive influence on job satisfaction; work environment has a significant and positive influence on job satisfaction; supervisor performance has a significant and positive influence on personnel performance; work environment has a positive and insignificant influence on personnel performance; job satisfaction has a significant and positive influence on personnel performance; supervisor performance has a significant influence on personnel performance through job satisfaction, and; the work environment does not have a significant influence on personnel performance through job satisfaction of personnel at the Surabaya Police Criminal Investigation Unit.